The experimental study on pyrolysis of cassava rhizome utilizing flue gas - Homchat K. (2017)
The characteristics during pyrolysis of cassava rhizome utilizing flue gas in a metal kiln have been studied experimentally. The pyrolysis parameters being studied include sample size, pyrolysis temperature and moisture content of the sample. The pyrolysis experiment include the dry and fresh cassava rhizome cylinders with 36, 40 and 44 mm. in diameter and the pyrolysis temperature varied from 400 to 500°C. The experimental result showed that the temperature distribution is caused by heat transfer from the surface to the inner cassava rhizome on both the radial and axial directions. The effect of the wood diameter and pyrolysis temperature affected the mass loss rate and the pyrolysis time. The large wood diameter caused lower mass loss rate and the pyrolysis time was longer. The higher temperature caused higher mass loss rate and shorter pyrolysis time. Fresh material need to be dried before pyrolysis can begin and more time is needed for the process. It was found that higher moisture in the fresh material yield more charcoal than that dry ones. In comparison between the experimental and the thermal gravimetric analysis (TGA) both mass loss during the process starting time are different. The mass loss of the pyrolysis by flue gas are more rapid when compared to the pyrolysis by TGA due to the effect on flue gas. In the experiment, the charcoal yield for the dry material varied from 26 to 35% depending on the pyrolysis temperature. It was found that the higher temperature caused lower the charcoal yield. © 2011 Published by Elsevier Ltd.